Pengaruh Penggunaan Model Problem Base Learning terhadap hasil belajar IPS di SD - julita, irmi; indrawati, tin; nasrul, drs (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to know the effect use of Problem Based Learning  model on student learning outcomes on the learning IPS at 5th grade of Elementary School Group Six Palembayan Subdistrict Agam District in the odd semester of the 2018/2018 school year. This research is a quantitative research with quasi eksperimental design. The population of this research is the students of 5th grade of elementary school in Group Six Palembayan Subdistrict Agam. The sample of this research is the 5th grade students of SDN 37 Tompek with the number of students 18 person and SDN 05 Kayu Pasak with the number of students 20 person. Sampling technique that is Nonprobabilty sampling with type Sampling Purposive. Based on the research that has been done, obtained tcount > ttable that is 7,71 > 2,03 with α = 0,05 so it can be concluded Ha accepted that there is influence the use of Problem Based Learning  model of student learning outcomes on the learning IPS at 5th grade of Elementary School Group Six Palembayan Subdistrict Agam District.Keyword : Problem Based Learning Model, IPS Learning, Learning Outcomes